ANALISIS KOMPARATIF DAN EKSPLORATIF TERHADAP KUALITAS PELAYANAN BANK SYARIAH DAN BANK KONVENSIONAL DI KOTA PEKALONGAN - Nalim (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2015)
For the last ten years, the focus for sharia trading industry has shifted from emphasising on price to service quality. Some of the reasons for this are: the rise of banking industry rivalry, stable business environment, more challenges faces, modern technology and the increasing number of service provider systems. Additionally, within the global market, the service quality has become more prominent in surviving the banking industry. Furthermore, the service quality also influences customers' satisfactory level. For these reasons, I am interested in researching further about service quality in banking industry. This study aims at (1) finding out factors that influence customers' banking choice (sharia and conventional banks), finding out service index comparison between sharia and conventional banks, and finding out the service quality difference between sharia and conventional banks. The instrument used to compare the service quality was SERVQUAL. The data was descriptively analysed and comparatively analysed using T-test. Descriptive analysis was employed to find out the emerging patterns within the data while the T-test was utilised to analyse the correlation among variables in the questionnaire. The result of the study indicated that there were four components (tangibleness, assurance, reliability and empathy) of the service quality which ranked the highest, scoring 3.69. The similar result of highest score of tangibleness, scoring 3.65, was also indicated for conventional bank. Additionally, the result of the study also indicated that sharia bank scored higher in terms of its quality on the point of 3.53, while conventional bank was on the point of 3.50.